Human Resources Management, Islamic Boarding Schools in Empowering Teachers in Jambi Province - Fuadi, Afif; Muntholib, Muntholib; Us, Kasyful Anwar; Mardayanti, Arlen (Dinasti International Journal of Management Science, 2024)
This study aims to analyze in depth about "Human Resource Management of Islamic Boarding Schools in Teacher Empowerment in Jambi Province (Case Study of Three Islamic Boarding Schools). This study uses a qualitative approach with data collection techniques using observation, interviews and documentation as supporting data. Data analysis techniques use qualitative techniques through domain analysis, taxonomy, and componential, and data is reduced, displayed and concluded. In the research process, the researcher is guided by the idea put forward by Fombrun, namely the process in Human Resource Management of Islamic Boarding Schools depends on selection, assessment, awards and development. The results of the study are that 1) Planning in these three Islamic Boarding Schools is adjusted to the needs of teachers and the number of male and female students; 2) The sources of teacher recruitment used in these three Islamic Boarding Schools are alumni of Islamic Boarding Schools, family and friends of teachers in the foundation only; 3) The types of training and development carried out are in the form of seminars, coaching in schools and foundations, further education, supervision by DIKNAS, training in developing teacher teaching methodology, MGMP (Subject Teacher Deliberation) schools, annual school work meetings, workshops; 4) Compensation and welfare of teachers in the three Islamic Boarding Schools vary. Some forms are also the same such as salary compensation, allowances, bonuses. However, in terms of nominal value, it differs between the three Islamic Boarding Schools. Based on the results of the study, it can be concluded that Human Resource Management of Islamic Boarding Schools in Teacher Empowerment in Jambi Province requires synergy from various policy makers.